Affiliation, Reward, and Punishment Relationships on Work Motivation for Nurses in the Emergency Room at Nashrul Ummah Islamic Hospital in 2022 - Amalia Alfi Karromallahu Darojat (Indonesian Journal of Humanities and Social Sciences, 2024)
The ability of a health facility as a whole is reflected in the ability of the Emergency Installation to provide quality health services so that it requires qualified and professional nursing staff. Quality and professional nursing care services can be achieved through good nurse performance. Various factors that influence performance greatly determine the results of a nurse's work, one of which is the nurse's motivation for the work they face. Nurse motivation is influenced by aspects of affiliation, reward and punishment To determine the relationship between affiliation, reward and punishment on nurses' work motivation in the Emergency Installation of the Islamic Nashrul Ummah Hospital in 2022. This research uses a cross-sectional method. Data analysis consists of Univariate and Bivariate analysis. The relationship between affiliation, reward and punishment on the work motivation of nurses in the emergency room at RSI Nashrul Ummah shows a significant relationship P < 0.05 (0.003 < 0.005). And the indicator that most influences motivation is affiliation. There is a significant relationship between affiliation, reward and punishment on the work motivation of nurses in the Emergency Room at the Islamic Nashrul Ummah Hospital. Suggestion: It is hoped that the results of this research can be used as information and consideration for the Nashrul Ummah Islamic Hospital.